Pengaruh Kinerja Mata Uang Rupiah dan Stok Bawang Putih terhadap Pembentukan Harga Bawang Putih di Pasar Tradisional Sukaramai Kota Medan - Sarah, Fauziah; Lubis, Fauzi Arif; Harahap , Muhammad Ikhsan (Medan Resource Center, 2022)
The purpose of this study was to determine the effect of rupiah currency performance and garlic stock on the formation of garlic prices in sukaramai traditional market, medan city. Quantitative methods and associative approaches are used in this study, questionnaires are used as data collection techniques, and the population and sample are 60 people. The data analysis method used multiple linear regression. The results of this study indicate that the Rupiah Currency Performance Variable (X1) has a significant effect on Price Formation which has been proven by the t-count value of 2,399. This value is greater than t table (1.67203) with a value of t sig (0.001) < 0.05, the garlic stock variable (X2) has a significant influence on price formation, this is evidenced by the t-count value of 4,066. This value is greater than t table (1.67203) with a value of t sig (0.000) < 0.05. Based on the results of the third hypothesis test, it is known that the significant value of 5.531 is greater than F table (2.77) with F sig (0.000) < 0.05. The results of this study indicate that the rupiah currency performance variable and Garlic Stock have a significant effect on the simultaneous formation of garlic prices.